Perancangan Sistem Informasi Penyebaran Lokasi UMKM Di Rantauprapat Dengan Web Gis - Ayuwandira, Syafira Dinda (Journal of Computer Science and Information System(JCoInS), 2022)
The determining factor for the success of SME management is the mastery of information technology. Technological progress is one of the theoretically accepted measures implemented to remove the barriers of economic frontiers because it helps to increase the productivity and efficiency of the economic factors of production of labor, capital and other resources, and increase the use of production inputs in production. With the existence of a Web GIS for MSMEs, it can make it easier for users to view and find out information from the MSMEs they want, as well as know the location of the MSMEs. Implementation of the program using the php programming language and mysql database. The results of the study are in the form of a web-based GIS for the location of MSMEs in Rantauprapat which can facilitate booking tour packages.